Cross-Religious Studies Curriculum at Theological Seminary: Case Study of The Islamology Implementation at Abdiel Theological Seminary - Ahmad Fahri Yahya Ainuri; Syamsul Ma’arif; Abdurrahman Mas’ud; Mirza Mahbub Wijaya (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
Abdiel Theological Seminary (STT) incorporates Islamic studies (Islamology) in its curriculum. This qualitative case study research explores the reasons behind teaching Islamology and the learning model adopted at the seminary. Furthermore, to analyze how the Islamology learning model is applied at Abdiel Theological Seminary and how it influences understanding, respect, and tolerance among religious believers. Data were collected through interviews, documentation, and observations during one semester from July to December 2019. Additionally, in October 2022, the researcher conducted follow-up interviews with colleagues to update the data. The learning model of Islamic Studies at Abdiel Theological Seminary contains various aspects that can support learning success. First, determination in learning planning by raising the themes according to the time's need and development. Implementing learning with open discussion activities inculcated a critical attitude towards all forms of information available, without any dogmatic attitude. Teaching Islamology at STT can generate understanding, respect, and tolerance among Muslim and non-Muslim citizens. The learning model focuses on contemporary Islamic religious phenomena, emphasizing critical thinking through open discussions without dogmatic attitudes. This approach contributes to constructive interactions among religious communities, promoting unity despite historical inter-religious conflicts.